CHANGING SCENARIO OF SUGARCANE DISEASES IN INDIA SINCE INTRODUCTION OF HYBRID CANE VARIETIES: PATH TRAVELLED FOR A CENTURY - Viswanathan, R (Journal of Sugarcane Research, 2019)
Sugarcane crop has been traditionally cultivated over centuries in India and other Asian countries for preparation of various sweeteners and to some extent for direct consumption. With the introduction of hybrid varieties, cane cultivation expanded to several regions in the country. During the expansion of the crop area, different disease problems have also been encountered; some were disastrous and decimated the industry very severely. The most important disease, which has hit hard the industry was red rot, caused by Colletotrichum falcatum Went and it destroyed cane cultivation by a series of epiphytotics in different decades for more than 100 years. Next to that, two other fungal diseases smut (Sporisorium scitamineum) and wilt (Fusarium sacchari) have also caused extensive damage to cane cultivation for the last 100 years. Since all the three pathogens damage stalk tissues, the economic losses due to them are always huge. Though these diseases could be managed by deploying resistant varieties now and then, they remain as a threat to the crop in some states. Other than these fungal diseases, foliar diseases such as rust, brown spot, eye spot, brown stripe, pokkah boeng etc were reported during different periods. Unlike the stalk infecting fungal diseases, the foliar diseases were seasonal in occurrence and mostly variety specific. Apart from fungal diseases many diseases caused by viruses, bacteria and phytoplasma were also made huge impact on performance of many sugarcane varieties during the previous decades. Important non-fungal diseases which caused substantial losses were grassy shoot, yellow leaf, mosaic, leaf fleck, ratoon stunting, leaf scald and red stripe. Many of these diseases became prominent after developing specific diagnostic tools in the recent years. Many management practices were developed to tackle the diseases, especially heat treatment of seed canes and virus elimination combined with molecular diagnostics became popular among the sugar industry.